1965
DOI: 10.1152/jappl.1965.20.1.164
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of bronchoconstriction during inhalation of sulfur dioxide

Abstract: Inhalation of SO2 (4–6 ppm) for 10 min decreased airway conductance (increased airway resistance) in seven healthy subjects. Subcutaneous injection of atropine prevented this effect. In anesthetized, paralyzed, artifically ventilated cats, SO2 increased pulmonary resistance, whether delivered to the upper or to the lower airways. This was prevented by complete cold block of the cervical vagosympathetic nerves or by injecting atropine intravenously before the SO2 was inhaled. These results establish the reflex … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
76
0

Year Published

1970
1970
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 232 publications
(79 citation statements)
references
References 0 publications
3
76
0
Order By: Relevance
“…Short-term exposure to NO2 could increase the bronchial tone by releasing histamine, as suggested by Nieding and Krekeler (16), or by stimulating the lung irritant receptors (17). Vagally mediated bronchoconstriction has been demonstrated for S02 (18), and the irritant receptors are thought to be hypersensitive in asthma (5). Such an increase in bronchial tone by N02 would explain the enhanced effect of carbachol since interaction between a bronchoconstrictor agent and increased airway tone would result in a potentiation of the effect of the bronchoconstrictor agent (19).…”
Section: Discussionmentioning
confidence: 89%
“…Short-term exposure to NO2 could increase the bronchial tone by releasing histamine, as suggested by Nieding and Krekeler (16), or by stimulating the lung irritant receptors (17). Vagally mediated bronchoconstriction has been demonstrated for S02 (18), and the irritant receptors are thought to be hypersensitive in asthma (5). Such an increase in bronchial tone by N02 would explain the enhanced effect of carbachol since interaction between a bronchoconstrictor agent and increased airway tone would result in a potentiation of the effect of the bronchoconstrictor agent (19).…”
Section: Discussionmentioning
confidence: 89%
“…The mechanisms producing bronchoconstriction in humans are relatively poorly understood, but are thought to involve stimulation of irritant receptors in the upper airway [6]. Atropine has been shown to block SO 2 induced bronchoconstriction in normal adults [7], suggesting a cholinergic re¯ex, but this agent is only partially effective in subjects with asthma [8]. Neither the difference in the sensitivity between asthmatics and normals to SO 2 , nor the differing effects of atropine blockade in these groups have been adequately explained.…”
mentioning
confidence: 99%
“…The question of the potential roles of the airway epithelial surface in host defence occurred to us in 1960 when we found that cigarette smoke (an environmental pollutant) particles are deposited on the epithelial surface exerting deleterious effects on lung function [5]. The potential roles of the epithelial luminal surface in epithelial defence returned to us a decade later, when we discovered that the community pollutants sulfur dioxide [6] and ozone [7] cause airway narrowing due to smooth muscle contraction.…”
Section: @Erspublicationsmentioning
confidence: 99%